Bioactive Compounds Enhance the Biocompatibility and the Physical Properties of a Glass Ionomer Cement - Aline Rogéria Freire de Castilho; Pedro Luiz Rosalen; Marina Yasbeck Oliveira; Jonny Burga-Sánchez; Simone Duarte; Ramiro Mendonça Murata; Regina Maria Puppin Rontani (Journal of Functional Biomaterials, 2024)
In order to characterize a novel restorative material, knowledge about the toxicological effect on human cells and the physical behavior of a glass ionomer cement (GIC) containing flavonoids was established. The flavonoids apigenin, naringenin, quercetin, and liquiritigenin were manually incorporated into a GIC. In the control group, no incorporation was performed. Two cell culture assays evaluated the toxicity of GICs: SRB and MTT. For both assays, the keratinocyte cell line (HaCaT) was exposed to GIC (n = 3/group) for 24 h. The physical properties of the GICs were evaluated by compressive strength (n = 10), surface roughness (n = 10), and hardness (n = 10) tests. Cell viability by SRB ranged from 103% to 97%. The control revealed a significant decrease in the metabolism of cells (61%) by MTT, while the GIC+apigenin slightly increased the succinic dehydrogenase activity (105%; p > 0.05), also confirmed microscopically. The compressive strength and roughness values were similar among groups, but the hardness increased after the incorporation of naringenin and quercetin into GIC (p < 0.05). The incorporation of flavonoids positively altered the biological and physical properties of the GICs.